O efeito disposição na indústria brasileira de fundos de investimentos em ações: um estudo empírico sobre os gestores brasileiros - Rodrigues, Marilú Rodriguez e (2016)
There is a representative number of studies showing evidence of the disposition effect. Such studies show that there are no explicit reasons for this deviant behavior, being a reason for doubt between rational and behavioral motivations. Shefrin and Statman (1985), in their seminal study developed the theory called the disposition effect, in which investors tend to sell winning assets quickly and loser assets remain active for longer. Although evidence of the disposition effect has been observed on these studies there are still gaps which have not been solved. Including the study of the disposition effect in emerging countries like Brazil, and studies with primary data which do not exist. The aim of this study is to evaluate whether Brazilian equity fund managers are affected by the disposition effect manifestation. The first empirical study with data from stock funds obtained from Economatica software took in consideration not only the portfolio of each fund every month, but also stock prices over time, assets of each fund and the Bovespa index. Along the study, several analysis were carried out, from statistical proportions tests to the adjustment of multivariate models such as logistic regression and ordered logistics to try to detect signs of the manifestation of the disposition effect on Brazilian equity funds managers. With all these techniques, we cannot neglect the presence of the disposition effect on the managers of the main Brazilian funds. The only test which showed no statistical significance was the test comparing proportion and market return. The difference on this test could have been influenced by the lack of fund assets control, which was held in regressions. The conclusion of the study shows that there is a disposition effect in Brazilian equity and investment fund managers, therefore the aim of the research survey has been met, as well as the data analysis performance made by Economatica software compared to previous studies such as Lucchesi (2010), where the author used data collected monthly by The Securities Commission of Brazil (2010). For further studies it is suggested that the research is carried out with the use of primary data from BM&FBOVESPA customers, as further from the evidence of the disposition effect it will be possible to identify the socioeconomic and demographic profile as well as other characteristics of the stock exchange Brazilian investor